Social Values and Measuring Consumer Behaviour - التير مصطفى (Dirasat in Economics and Business, 1978)
The search for culturally free measurements has been, for a long time, the major goal of many social Scitntiste. Some social Scientists focused on cross-national research. They assumed that utilizing comparable data from different countries would lead, eventually to measurements capable of measuring social phenomena regardless of geographical location. However, cross-national research is quite compicated, difficult, and needs careful planing. The present paper reports on some of the compications cross-national research faces. It reports on some of the problems encountred in the process of developing cross-nationl measurement of consumer behaviour. Data used here from a cross-national study of mod-ernization which involves: Finland, Libya, New Zealand. Peru. Poland, and The United States. A scale of consumer ownership and consumer asperation was included in the general in study. To develop the scale a battery of thriteen items was prepared . It included house, apartment, television, radio, automobile, a really eleqent home, vacation home, colour television, trips aboard, refregerator, recoard player , live-in househeld help and telephone. The respondent was to indicate weather he already had the item, planned to have it, hoped to have it or did not care to have it. Analysis of data revealed that individuals in the six countries involved evaluate the thriteen consumer goods differently. Thus, the battery of the thriteen consumer items does not produce a comparable international measure-ement of consumer aspiration. While consumer goods ownership is an international phenomenon, consumer items have different social values and degree of desirability in different societies. Therefore, cross-national measurement of consumer behaviour should include only goods which have similar social values in the societies involved.